Engineering and Artificial Intelligence for Sustainable Development and Nation Building (Comprehensive Journal of Science, 2026)
This research paper examines the complementary relationship between engineering and artificial intelligence in supporting sustainable development and state-building. The study highlights their vital role in managing natural resources, enhancing energy efficiency, developing smart infrastructure, and achieving the Sustainable Development Goals (SDGs).The paper presents practical examples from various countries and recent statistics demonstrating the tangible impact of these technologies on critical sectors such as water, energy, health, education, and the economy. It also addresses the challenges related to AI and modern engineering adoption, proposing practical strategies to overcome these obstacles.
Keywords: Engineering, Artificial Intelligence, Sustainable Development, State-Building